Implementasi Algoritma RSA Untuk Keamanan Data Kredit di PT Bank Perkreditan Rakyat Solider Pematangsiantar - Ferdinal Rahmat Gea; Sumarno Sumarno; Zulaini Masruro Nasution; Dedy Hartama; Jalaluddin Jalaluddin (BEES: Bulletin of Electrical and Electronics Engineering, 2021)
Bank is a business entity that collects funds from the public in the form of savings and distributes them to the public in the form of credit. PT. Bank Perkreditan Rakyat Solider has a data system that can only be known by certain parties. Data security is one of the most important things to consider in maintaining the confidentiality of important data collection information, an additional security technique is needed with the aim of maintaining the confidentiality of this important information. Without additional techniques to maintain data confidentiality, many unauthorized parties can carry out attacks, one of which is data theft. The RSA algorithm is an appropriate security technique because it uses a pair of keys with a high level of difficulty in factoring numbers into prime factors. With the RSA Algorithm method, customer credit data at PT. Solider People's Credit Bank is kept confidential.